2017
DOI: 10.1007/s11010-017-3180-0
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin-dependent internalization, signaling, and metabolic processing of guanylyl cyclase/natriuretic peptide receptor-A

Abstract: Cardiac hormones, atrial and brain natriuretic peptides (ANP and BNP), have pivotal roles in renal hemodynamics, neuroendocrine signaling, blood pressure regulation, and cardiovascular homeostasis. Binding of ANP and BNP to the guanylyl cyclase/natriuretic peptide receptor-A (GC-A/NPRA) induces rapid internalization and trafficking of the receptor via endolysosomal compartments, with concurrent generation of cGMP. However, the mechanisms of the endocytotic processes of NPRA are not well understood. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…In recent studies using 125 I-ANP binding assay and confocal microscopy, we have examined the role of dynamin in the internalization and trafficking of NPRA in a stably transfected HEK-293 cells [69]. Our findings indicated that ANP treatment of high-density NPRA expressing recombinant HEK-293 cells time-dependently accelerates internalization of receptor from the plasma membrane to the cell interior.…”
Section: Role Of Dynamin In Npra Endocytosismentioning
confidence: 82%
See 4 more Smart Citations
“…In recent studies using 125 I-ANP binding assay and confocal microscopy, we have examined the role of dynamin in the internalization and trafficking of NPRA in a stably transfected HEK-293 cells [69]. Our findings indicated that ANP treatment of high-density NPRA expressing recombinant HEK-293 cells time-dependently accelerates internalization of receptor from the plasma membrane to the cell interior.…”
Section: Role Of Dynamin In Npra Endocytosismentioning
confidence: 82%
“…4). Moreover, IF visualization of the internalization of NPRA and enhanced GFP-tagged NPRA in HEK-293 cells by confocal microscopy have demonstrated the formation of endocytic vesicles after 5 min of ANP treatment; this effect was blocked by clathrin inhibitors (MDC and CPZ) and mutant dynamin construct [69]. These studies showed that NPRA undergoes internalization via clathrin-mediated endocytosis as part of its normal cellular itinerary, including receptor trafficking, signaling, and metabolic degradation.…”
Section: Role Of Dynamin In Npra Endocytosismentioning
confidence: 92%
See 3 more Smart Citations